2010
DOI: 10.1016/j.rmed.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CPAP therapy on the sympathovagal balance and arterial stiffness in obstructive sleep apnea

Abstract: Improvement of the sympathovagal balance by CPAP therapy may be significantly related to decreased stiffness of the central to middle-sized arteries, independent of the changes in the blood pressure and vascular endothelial status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…[11][12][13][14][15] In the present Long-term effect of CPAP for PWV in sleep apnea T Saito et al study, PWV in both NT and HT patients decreased initially before increasing gradually: during the initial 6 months of treatment, PWV decreased significantly and then increased gradually over the next 18 months. Despite the gradual increase in PWV over the final 18 months of treatment, PWV after 2 years of CPAP in both groups remained below baseline values.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…[11][12][13][14][15] In the present Long-term effect of CPAP for PWV in sleep apnea T Saito et al study, PWV in both NT and HT patients decreased initially before increasing gradually: during the initial 6 months of treatment, PWV decreased significantly and then increased gradually over the next 18 months. Despite the gradual increase in PWV over the final 18 months of treatment, PWV after 2 years of CPAP in both groups remained below baseline values.…”
Section: Discussionmentioning
confidence: 48%
“…10 A few recent studies showed that CPAP effectively improved PWV when used for short periods of time. [11][12][13][14][15] However, the long-term effects of CPAP on PWV remain unclear. Previous studies of the short-term effects of CPAP on PWV were performed in normotensive (NT) OSA patients; thus, the effects of CPAP on PWV in patients with HT are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found a significant correlation between the severity of sleep apnea, as measured by arousal index, and baPWV. Similarly, Shiina et al 63 found 3 months of CPAP to lead to a significant decrease in baPWV but not peripheral blood pressure. Saito et al, 64 however, found 6 months of CPAP treatment to decrease both baPWV and peripheral blood pressure in both hypertensive and normotensive patients.…”
Section: Resultsmentioning
confidence: 90%
“…Sleep apnea is also a risk factor for accelerated increase of the brachial-ankle PWV 32,33) . Sympathetic nervous activation induced by hypoxia resulting from apnea may be one of the mechanisms underlying the accelerated increase of the arterial stiffness in subjects with sleep apnea 34) . Although several cross- 46) , subclinical cerebral damage 47) , cognitive dysfunction 48) , renal dysfunction 49,50) , cardiac diastolic dysfunction 51) , left ventricular hypertrophy 52) , and/or increased carotid intima-media thickness 53) ].…”
Section: Metabolic Syndrome Sleep Apnea and Obesitymentioning
confidence: 99%